Effect of knee extension constraint training on walking biomechanics 6 months after anterior cruciate ligament reconstruction: a double-blind randomized controlled clinical trial - Tianyu Gao; Hongshi Huang; Yuanyuan Yu; Hui Liu; Yingfang Ao (Journal of Orthopaedic Surgery and Research)
Abstract Background The incidence of knee osteoarthritis after anterior cruciate ligament reconstruction (ACLR) is high to 57%, and the biomechanical abnormality during walking is one of the reasons. The purpose of this study was to investigate the effect of 12 weeks of knee extension constraint training on walking biomechanics during the stance phase of injured side after ACLR. Methods Forty-five patients were randomly assigned to three groups based on different brace conditions from 13 weeks to 24 weeks after ACLR: experimental (brace with knee extension constraint), placebo (brace without knee extension constraint), and control (no brace). Gait analysis was performed 3 and 6 months after ACLR. The peak for knee flexion angle (KFA), knee extension moment (KEM), and vertical ground reaction force (vGRF) were compared by 2 (time) x 3 (group) repeated-measures analysis of covariance (ANCOVA), and pairwise comparisons were conducted. . Results There was a significant time x group interaction for the peak KFA (p = 0.047), and there was no significant time x group interaction for the peak KEM and peak vGRF. The pairwise comparisons showed that there were no statistical differences among the groups both the pre-intervention and post-intervention in the peak KFA, peak KEM, and peak vGRF. Compared with pre-intervention, the peak vGRF in the experimental group was significantly greater (p = 0.009) and the peak KFA in the control group was significantly lower (p = 0.041) post-intervention. There were not significantly different in the placebo group between pre-intervention and post-intervention. Conclusion 12 weeks of knee extension constraint training can increase lower extremity loading on the injured side, may be a potential therapeutic adjunct to improve abnormal gait after ACLR.